2013
DOI: 10.1007/s12032-013-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

Cullin 4B is a novel prognostic marker that correlates with colon cancer progression and pathogenesis

Abstract: Cullin 4B (CUL4B), a scaffold protein of the Cullin4B-RING E3 ligase complex, functions in proteolysis. The present study aims to investigate its expression pattern and evaluate whether CUL4B expression was associated with histopathological and prognosis in the patients with colon cancer. Real-time PCR and western blot were used to identify CUL4B expression in tumor tissue and the paired adjacent normal mucosa from patients with colon cancer. Immunohistochemistry on a tissue microarray containing 203 cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 24 publications
2
51
0
1
Order By: Relevance
“…CUL4B has recently been shown to be highly expressed in a variety of human malignancy and is positively correlated with tumor progression (25,26,29,39,40). In the current study, we demonstrated that CUL4B functions to limit the expansion and activity of MDSCs that are an integral part of the immunosuppressive tumor microenvironment.…”
Section: Discussionsupporting
confidence: 61%
“…CUL4B has recently been shown to be highly expressed in a variety of human malignancy and is positively correlated with tumor progression (25,26,29,39,40). In the current study, we demonstrated that CUL4B functions to limit the expansion and activity of MDSCs that are an integral part of the immunosuppressive tumor microenvironment.…”
Section: Discussionsupporting
confidence: 61%
“…High expression of CUL4B expression was reported to be related to tumor histological differentiation, invasion, distant metastasis, tumor size, lymph node metastasis, overall and recurrence rate, as well as disease-free survival in breast, colorectal, cervical, oesophageal and lung cancers [3, 18, 20, 27]. Study has shown that knockdown CUL4B could suppress the epithelial–mesenchymal transition (EMT) progress [28].…”
Section: Cul4b Expression In Human Cancersmentioning
confidence: 99%
“…In the colorectal epithelium, cells turn over quickly and are exposed to various DNA adduct-forming molecules found in charcoal, fried food, and cigarette smoke. Analysis of a large cohort of colorectal cancer patients in China showed that tumor cells have higher CUL4B expression than surrounding normal mucosal cells and that high CUL4B expression (both mRNA as well as protein) correlates with tumor invasiveness, metastasis, more advanced tumor stages and poorer prognosis (Jiang et al, 2013). Another study showed that CUL4B protein and transcript levels are higher in colorectal cancers (Hu et al, 2012).…”
Section: Clinical Relevancementioning
confidence: 99%